Compromised MPS1 Activity Induces Multipolar Spindle Formation in Oocytes From Aged Mares: Establishing the Horse as a Natural Animal Model to Study Age-Induced Oocyte Meiotic Spindle Instability - Rizzo, Marilena; Stout, Tom A. E.; Cristarella, Santo; Quartuccio, Marco; Kops, Geert J. P. L.; De Ruijter-Villani, Marta (Frontiers in Cell and Developmental Biology, 2021)
Aneuploidy originating during meiosis in oocytes is the major cause of reduced fertility, implantation failure and miscarriage in women beyond their mid-thirties. Loss of chromosome cohesion, and defective microtubule dynamics and spindle assembly are, in turn, the major contributors to the error-prone nature of chromosome segregation in the oocytes of older women. However, the underlying molecular defects are not well understood. Altered function of MPS1 and AURKC have been shown to induce multipolar spindle phenotypes in murine oocytes and cancer cells, however their role in reproductive aging associated oocyte aneuploidy is not known Although age-related gamete and embryonic aneuploidy has been studied in female rodents, the horse may be a more appropriate animal model. Similar to women, aged mares suffer from reduced fertility and an increased incidence of oocyte aneuploidy. Moreover, mares show a long interval (decades) to reproductive senescence and, unlike rodents but similar to women, horse oocytes assemble the meiotic spindle in a slow and unstable manner, independent of microtubule organizing centers. In this study we found that oocytes from aged mares have lower expression of mRNA for Mps1 and AurkC than oocytes from young mares while gene expression for other meiosis regulators did not differ. To assess the ability of horse oocytes to correctly form a bipolar spindle, in vitro matured MII oocytes were allowed to re-form their spindle after nocodazole-induced microtubule depolymerization. To investigate the importance of MPS1 and AURKC function in spindle (re)assembly, various concentrations of a MPS1 inhibitor (MPS1i, Compound 5) or an AURK inhibitor (AURKi, ZM447439) were included after nocodazole washout. MII oocytes from aged mares showed a higher incidence of spindle abnormalities after exposure to MPS1i. In contrast, Aurora kinase inhibition severely impaired microtubule organization and spindle formation in all oocytes, irrespective of mare age. In conclusion, gene expression for the kinases Mps1 and AurkC is reduced in oocytes from aged mares. Moreover, spindle (re)assembly in aged mares’ oocytes is more unstable when Mps1 is inhibited. Overall, this suggests that compromised Mps1 activity predisposes to meiotic spindle instability in aged mare oocytes. This spindle instability could predispose to chromosome segregation errors.